2018
DOI: 10.5194/gmd-11-4711-2018
|View full text |Cite
|
Sign up to set email alerts
|

The use of radiocarbon <sup>14</sup>C to constrain carbon dynamics in the soil module of the land surface model ORCHIDEE (SVN r5165)

Abstract: Abstract. Despite the importance of soil as a large component of the terrestrial ecosystem, the soil compartments are not well represented in land surface models (LSMs). Indeed, soils in current LSMs are generally represented based on a very simplified schema that can induce a misrepresentation of the deep dynamics of soil carbon. Here, we present a new version of the Institut Pierre Simon Laplace (IPSL) LSM called ORCHIDEE-SOM (ORganizing Carbon and Hydrology in Dynamic EcosystEms-Soil Organic Matter), incorp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The above-noted discrepancies between the simulation and the observation highlight both the need for more peat core data collected with more rigorous sampling methodologies and the need to improve the model. In parallel with this study, 14 C dynamics in the soil have been incorporated into the ORCHIDEE-SOM model (Tifafi et al, 2018), which may give us an opportunity to compare simulated 14 C age-depth profiles with dated peat C profiles in the future after being merged with our model.…”
Section: Vertical Profiles Of Peatland Soil Organic Carbonmentioning
confidence: 99%
“…The above-noted discrepancies between the simulation and the observation highlight both the need for more peat core data collected with more rigorous sampling methodologies and the need to improve the model. In parallel with this study, 14 C dynamics in the soil have been incorporated into the ORCHIDEE-SOM model (Tifafi et al, 2018), which may give us an opportunity to compare simulated 14 C age-depth profiles with dated peat C profiles in the future after being merged with our model.…”
Section: Vertical Profiles Of Peatland Soil Organic Carbonmentioning
confidence: 99%
“…Measurements of radiocarbon offer great potential to constrain temporal dynamics of the land carbon cycle in ESMs as well as to assess their performance. However, to date, such comparisons have been limited to a small number of models that simulate C isotopes (e.g., Chen et al, ; Koven et al, ; Tifafi et al, ), as the majority of models do not explicitly represent isotope dynamics. The current coupled climate‐carbon cycle model intercomparison project (C4MIP) of the Coupled Model Inter‐comparison Project Phase 6 (CMIP6) requests model participants to explicitly model radiocarbon and include the corresponding output from the major land and ocean model compartments (Graven et al, ; Jones et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In calibrating the ORCHIDEE-SOM model, Guenet et al (2013) found that including vertical SOC transport was important for accurately simulating the changes in SOC concentrations of bare fallow sites. Using a similar version of ORCHIDEE-SOM model, Tifafi, Camino-Serrano et al (2018) found that varying the SOC diffusion coefficient with soil depth improved the simulated SOC concentration and 14 C profiles. However, Huang et al (2018) found that the carbon input was more important than vertical transport in simulating vertical SOC profiles using a different version of ORCHIDEE, ORCHIDEE-MICT.…”
mentioning
confidence: 99%
“…Only a limited number (probably <3) of vertically resolved soil carbon models with nonlinear kinetics for soil carbon decomposition have been developed, such as the model COMISSION by Ahrens et al (2015), which was recently improved by including additional processes and nutrient cycles (Yu et al, 2020). Most of these models were evaluated using the data from a limited number of sites (<15) (see Koven et al, 2013;Tifafi, Camino-Serrano et al, 2018). Given the usually poor performance of soil carbon models (Todd-Brown et al, 2013), which likely leads to diverging responses of soil carbon to future climate change predicted by ESMs (Wieder et al, 2013), it is necessary to calibrate these models for different ecosystem types and across a wide range of environmental conditions before applying them globally.…”
mentioning
confidence: 99%